Characterisation of CIS- and trans-acting factors that regulate the human alpha 2(1) procollagen gene - Masemola, Agatha Maripanyane (Division of Medical Biochemistry, 2023)
The differential expression of the a2(I) procollagen gene in normal and transformed human fibroblasts has been correlated with differential in vitro DNA-protein interactions on the basal promoter region between -100 and -67. A 23 bp region of the a.2(1) procollagen promoter encompassing the G/CBE (CCTCCATTGG) and the Ctv'IE (GGAGGCCCTTTT) has previously been shown to engage in specific DNA protein interactions that determined the transcriptional activity of the promoter. The CME forms two distinct DNA-protein complexes that might be crucial in the regulation of the a2(I) procollagen gene in a cell specific manner. The hypothesis was, therefore, that depending on the protein that participates in complex formation with the CME, the gene would be activated or repressed. The objective of this study was to investigate the role of this 23 bp region in the regulation of expression. of the a2(I) procollagen gene in transformed fibroblasts. In addition, the study sought to establish the role of the proto-oncogene c-fos-in the regulation of expression of the a2(I) procollagen gene. In contrast to previous observations, this study demonstrated that only one DNA protein complex is formed on the CME and the second complex is a specific proteolytic cleavage of the product of the larger complex. Preparation of nuclear extracts in the absence of protease inhibitors, specifically leupeptin, resulted in the formation of a smaller complex, previously shown to bind the CME. The importance of this proteolytic fragment that still retains DNA binding activity is yet to be determined. In addition, the CME binding proteins were fairly ubiquitously expressed in both a.2(1) collagen producing and non-producing cells. CT-1 fibroblasts (transformed by y-irradiation) synthesise over 80% of total a2(I) collagen produced by its untransformed counterpart (WI-38 fibroblasts), whereas the gene, is down regulated in the human embryonic lung fibroblasts transformed with SV40 (SVWI-38 fibroblasts). These cell lines are therefore ideal for studying regulation of a.2(I) procollagen gene. To analyse the importance of the G/CBE and CME regions of the a.2(1) procollagen gene promoter, point mutations were introduced by site-directed mutagenesis. Mutated promoter DNA was cloned into a p8CAT reporter vector, and the activity of the promoter determined in transient transfection experiments. Mutations introduced in the G/CBE region of the a.2(1) procollagen promoter resulted in a 3-12-fold decrease in the activity of the promoter. The decrease was observed with both proximal (-343 bp) and basal (-107 bp) promoter constructs~ a significant reduction in promoter activity was observed in both CT-1 and SVWI-38 fibroblasts. These results imply that the G/CBE region of the promoter is required for the activation of transcription of the a.2(1) procollagen gene and therefore the factor that interacts with the G/CBE functions as a transcriptional activator. Previously, this factor was shown to complex with antibodies raised against the mouse CCAAT binding factor (CBF), suggesting that the protein belongs to the CBF family of transcription factors. Furthermore, these results demonstrate that the adjacent, upstream inverted GGAGG sequence is crucial for activation of the gene through the CCAAT binding element. The inhibition of promoter activity in constructs with a mutated G/CBE element was correlated with lack of protein binding to the mutated sequence as confirmed by electrophoretic mobility shift assays. Transfection of a.2(1) procollagen promoter constructs containing mutations in the CME region, however, resulted in a significant increase in promoter activity in both CT-1 and SVWI-38 fibroblasts. A much higher increase, 3-fold, was observed for the SVWI-38 cell line compared to a 1.5-fold increase observed for CT-1 fibroblasts. These results suggested that the factor that interacts with the CME functions as a repressor of the a.2(1) procollagen gene. Interestingly, the promoter activity in SVWI38 fibroblasts transfected with mutated CME constructs was similar to that observed in CT-1 fibroblasts transfected with the wild type promoter construct. An interesting observation was that repression of the a.2(1) procollagen gene via the CME required upstream elements since transfection of the basal mutated promoter did not result in increased promoter activity. From these results, it can be concluded that the CME binding protein is involved in cell-specific repression of the a2(I) procollagen gene and that the mechanism of repression appears to be dependent on the presence of upstream elements. Mutations in the G/CBE and CME pointed out the significance of these elements in the expression of the a2(I) procollagen gene and since a number of studies have characterised the mouse CCAAT binding protein, this study focused on purification and identification of the CME binding protein(s). Purification was performed by conventional biochemical techniques using heparin-agarose and sequence-specific DNA affinity chromatography, as well as separation on SDS-polyacrylamide gels. Two cycles of DNA affinity chromatography yielded two polypeptides with apparent molecular weights of 50 and 67 kDa. Automated N-terminal sequencing of the polypeptides indicated that they were blocked and therefore no sequence could be obtained. In addition, these polypeptides failed to raise an immune response in mice and rabbits. Subsequently, polypeptides were digested with trypsin in situ in polyacrylamide gels and the eluted peptides were analysed by MAWITOF-mass spectrometry. The mass:charge ratios (mlz ratios) obtained were used to search the database using a mass tolerance of 1.5 Da and only one hit was obtained. The match obtained was that of a mouse zinc finger protein of which not much is known, except that it might be a transcription factor. This result supports previous observations of Collins et al (J Cell Biochem 1998, 70: 455-467) that complex formation requires the presence of zinc. The primary structure of the CME binding protein remains to be determined. Transformation of fibroblasts is normally accompanied by changes in the expression of extracellular proteins, including type I procoUagen. Although CT-I fibroblasts, show very little change in a2(I) procollagen gene expression, the c-f os gene is drastically down-regulated. This study sought to establish if there is any relationship between the unusually high levels of the a2(I) procollagen gene in this transformed cell line and failure of the cells to stimulate c-fos expression in response to serum. CT-1 :fibroblasts that overexpressed wild type Fos were established and changes in the expression of the a,2(1) procollagen gene were measured. Overexpression of Fos down-regulated the a,2(1) procollagen gene, which was not due to increased turnover of the a1(I) procollagen mRNA. Analysis of promoter activity showed that the promoter and first intron, which has been reported to contain negative regulatory elements, did not harbour any Fas-responsive elements. The -343 bp and the -2300 bp promoter constructs were transactivated in cells overexpressing Fos. Thus, although overexpression of Fos resulted in a significant decrease in the levels of the a2(1) procollagen WA, it does not involve the region between -2300 bp and +1800 bp of the a2(1) procollagen gene. Furthermore, there was no change in the stability of the message, indicating that constitutive expression of Fos did not activate a factor that could play a role in altered turnover of the a2(I) procollagen mRNA. It is therefore possible that constitutively high levels of Fos may trigger the expression of a number of other genes, which have a negative impact on the expression of the a2(I) procollagen gene.